(3cfR GdbfGYI aj Yde GdUfGYIs - (3GdNhfSGQj GdTjYj, Rjf GdYGHOjf GHf eMeO HGbQs ((3cJHNGfI fhQ YKeGfjIs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf aEfj LeYJ gPG GdeNJGQ hGfJNHJg ef cdGe GdMceGA GdeJbOejf heLQHGJge hGNJUQJg hPcQJ cd eG jLH Yd GdWGdH eYQaJg djYjfg Ydi eWdhHg hfYJg H s
(3BNQgG (B:s
(3hRQfjN CMeQ hbdj ef cd hGMO LRA hcHQjJ CUaQ CQHYI CLRGA hRGL CUaQ LRFjf hHhQb LRA hfcGQ LRA jSMb GdLejY SMbG HdjZG hjPGH hjWGYe GdHhQb JeJ GdSHYI CHhGHs
(3JHUQI GdeDda (B:s
(3UGMH CfjS GdeTJZdjf ; EjVGM Gdecfhf (B2\ 386s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf (B2\ 386s
(3EjVGM Gdecfhf (B2\ 386s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs